Cardiac Transthyretin Amyloidosis: Hidden in Plain Sight - Constantine N. Logothetis; Joel Fernandez; Damian A. Laber (Case Reports in Medicine)
Amyloidosis is an underappreciated medical condition with symptoms camouflaging as common medical comorbidities leading to its underdiagnosis due to its systemic involvement. Despite common misconceptions, amyloidosis and its systemic comorbidities are more prevalent and treatable than previously acknowledged by the medical community. There are two major forms of amyloidosis: amyloid light-chain and transthyretin amyloidosis. Each of these have a distinct pathophysiology, diagnostic work-up, treatment, and prognosis. The patient described in this study was diagnosed with transthyretin cardiac amyloidosis months after presenting with heart failure of unknown etiology. Usually, clinicians presume that heart failure results from common comorbidities such as hypertension, diabetes, and hyperlipidemia. Here, the correct etiology was transthyretin cardiac amyloidosis. The patient had five admissions for heart failure symptoms prior to a physician identifying the etiology as cardiac transthyretin amyloidosis. After initiating the transthyretin stabilizer tafamidis, the patient did not experience another heart failure exacerbation. This vignette provides an example of the clinical presentation, diagnostic work-up, and treatment of a patient with cardiac transthyretin amyloidosis. The review of the literature focuses on the epidemiology, and clinical symptoms that should prompt an evaluation for cardiac amyloidosis as well as the diagnostic and therapeutic options are available. Transthyretin cardiac amyloidosis is a rare and underdiagnosed disease, while heart failure is a highly prevalent condition. This clinical vignette seeks to provide education and awareness to an overlooked medical disorder.